Conceptual design of a multifunctional barbeque set - Rashid, Syukri Amin; Nazri, Syahminisa Binti Nazri; Rafik Ahmad, Ahmad Nabil Arif; Shaharin, Syasya Umira; Chong Qianlun, Dmitri Luping; Manssor, Nur Aini Sabrin (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
Addressing the limitations of conventional BBQ sets, which often lack user-friendly features and are limited to basic grilling functions, this project focuses on developing a conceptual design that integrates a griller and a skewer attachment. The design process involves utilizing SolidWorks software for modeling and analyzing the BBQ set design, with careful consideration given to material selection to ensure durability and safety. By combining innovative design elements with a focus on functionality and material quality, this conceptual BBQ set seeks to establish a new standard in the market, providing consumers with a versatile option that meets a variety of needs. This project represents a significant advancement in improving the BBQ experience and aligning with the changing preferences of consumers.